Illegal logging dalam Prespektif Islam: (Penerapan Konsep Maslahah dalam Masalah Lingkungan Menurut Al-Syâthibî dalam Kitab Al-Muwâfaqât) - Muksin, Asep (Siyasyatuna | Jurnal Hukum Tata Negara, 2024)
Illegal logging is a problem that cannot be solved. This activity causes damage to forest ecosystems which will have a negative impact on human life. The solution presented for this crime is the enactment of Law no. 41 of 1999 and Law no. 41 18 of 2013 concerning the prevention and eradication of forest destruction. However, this crime continues to occur and even increases from year to year. This study elaborates the spirit of the Qur'an in responding to the above problems with the ushul fiqh approach with the concept of maslahah according to Al-Syâthibî in his book Al-Muwâfaqât. The method used in this paper is to use the method of content analysis (content analysis) and descriptive analysis (descriptive analysis). Based on this study, it can be concluded that according to qiyâs al-Isthinbhâthy, illegal logging is strictly prohibited in religion. He violates the principle of benefit dharuriyyat such as always taking care of the soul. Illegal logging is a crime that can threaten the human soul.